Zwangsjacke Euro. Die Fehlkonstruktion des Europäischen Economic Governance-Systems - Heise, Arne (Wirtschaft und Gesellschaft, 2014)
The persistence of the European Monetary Union (EMU) is being questioned from all different political and economic orientations arguing that it is not in the economic interest of its member states to maintain the EMU but involving costs that could be avoided if EMU would be abandoned. In stark contrast to these opinions, most actors that are politically responsible cling to the project Euro and the European Commission even believes that the European Economic Governance System (EEGS), in which the Eurozone is embedded, is the institutionalized guarantor of stability of the real economy in an environment which has become more instable after the World Financial Crisis after 2008. This paper argues that - contrary to the European Commission’s claim - the EEGS has failed in managing the aftermath of the World Financial Crisis appropriately and that it has turned the Euro into a straightjacket which threatens to strangle some its member state.